2009
DOI: 10.4049/jimmunol.0801792
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Renders Conventional Lymphocytes Resistant to Suppressive Functions of Regulatory T Cells through Activation of the Phosphatidylinositol 3-Kinase Pathway

Abstract: International audienceIL-15 drives chronic inflammation in several human diseases. We have recently shown that IL-15 inhibits the immunosuppressive effects of TGF-beta through blockage of the Smad3-signaling pathway. Data pointing to reciprocal interactions between TGF-beta and CD4(+) regulatory T cells led us to investigate the impact of IL-15 on the de novo generation and function of regulatory T cells in humans. Our data indicate that IL-15 does not counteract, but rather promotes the effect of TGF-beta on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 48 publications
5
99
2
4
Order By: Relevance
“…Our own data in hIL-15TgE mice suggest that IL-15 alone is not sufficient to impair the conversion of naïve CD4+ T cells into Tregs [23]. However, in agreement with previous work, we observed that IL-15 rendered human effector CD8+ T cells and, at a lesser degree, memory CD4+CD45RO+ T cells, insensitive to the immunosuppressive effects of Tregs [52]. This mechanism likely operates in CD, as intestinal and peripheral T cell from active CDs, notably CD8+, responded less well in vitro to suppression by autologous or heterologous Tregs [53,54].…”
Section: Il-15 Can Participate In Multiple Steps Of CD Pathogenesissupporting
confidence: 76%
“…Our own data in hIL-15TgE mice suggest that IL-15 alone is not sufficient to impair the conversion of naïve CD4+ T cells into Tregs [23]. However, in agreement with previous work, we observed that IL-15 rendered human effector CD8+ T cells and, at a lesser degree, memory CD4+CD45RO+ T cells, insensitive to the immunosuppressive effects of Tregs [52]. This mechanism likely operates in CD, as intestinal and peripheral T cell from active CDs, notably CD8+, responded less well in vitro to suppression by autologous or heterologous Tregs [53,54].…”
Section: Il-15 Can Participate In Multiple Steps Of CD Pathogenesissupporting
confidence: 76%
“…Both IL-7 and IL-15 were shown to reverse suppression by Tregs (28,29). Moreover, it was reported that when IL-7 is used in combination with IL-2 for longterm expansion of Tregs, the expanded population showed increased proliferation and reduced suppressive capacity (30).…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 supports basal proliferation and survival of CD81 memory T cells (Sandau et al, 2010), and dual roles of IL-15 on the function of regulatory T cells (Treg) have been reported. Although IL-15 has the potential to promote regulatory T (Treg) cell function (Ben Ahmed et al, 2009;Xia et al, 2010), it can also have the opposite effects (Ben Ahmed et al, 2009). IL-15 can induce responses through a mechanism called trans-presentation (Stonier et al, 2010), suggesting a very local effect that depends on the cells and factors present in the surrounding microenvironment.…”
Section: Discussionmentioning
confidence: 99%